Selected letters of Clive Bell : art, love and war in Bloomsbury - Bell, Clive, 1881-1964; Hussey, Mark, 1956- (Edinburgh : Edinburgh University Press, 2023)
A selection of letters by the pacifist and noted art critic Clive Bell, expertly annotated by his biographerIllustrates a comprehensive range of Bell's interests and relationshipsOffers a unique record of a transformative time in the cultural and political history of the WestArranged in eight categories to afford readers guidance in how to approach the varied emphases of Bell's life and interests, as well as highlighting what is particularly significant, such as his close lifelong relationship with Virginia WoolfClive Bell was a pivotal member of the Bloomsbury Group. His marriage to Vanessa Bell and his, at times tempestuous, relations with his sister-in-law Virginia Woolf form important strands in the cultural history of modernism. A tireless champion of modernist art, a committed pacifist and conscientious objector, Bell produced a huge body of correspondence with many of the leading artistic and political figures of his time. His lively, witty, highly opinionated letters are a window into the turbulence of the early twentieth century, populated by friends and acquaintances including T. S. Eliot, Katherine Mansfield, Pablo Picasso and Jean Cocteau, as well as his Bloomsbury set, Desmond MacCarthy, Leonard and Virginia Woolf, Duncan Grant, Maynard Keynes, Roger Fry and Vanessa Bell. Arranged in eight categories - Bloomsbury Circles; Virginia; War; Arts and Letters; To the Editor; Francophile; Travels; Love, Gossip, Home - this selection emphasises Bell's enormously varied life and interests. Born in the reign of Queen Victoria and living long enough to have been able to hear the Beatles on the radio, these letters demonstrate that Bell's appetite for art, for love and for peace never flagged.
Frontmatter -- Contents -- Acknowledgements -- Editorial Practices -- Abbreviations -- Addresses -- People -- Chronology -- Books and Pamphlets by Clive Bell -- Introduction -- 1. Bloomsbury Circles -- 2. Virginia -- 3. War -- 4. Arts and Letters -- 5. To the Editor -- 6. Francophile -- 7. Travels -- 8. Love, Gossip, Home -- Index
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Bell, Clive, -- 1881-1964 -- Correspondence; Bell, Clive, -- 1881-1964; Art critics -- Great Britain -- Correspondence; Critiques d'art -- Grande-Bretagne -- Correspondance; ART / Criticism & Theory; Art critics; Great Britain; Electronic books; Personal correspondence